Nature-Based Solutions in Island Water Management: A Case Study From Bozcaada (Türkiye) - Baba, Alper; Samiloglu, Bilgesu; Gündüz, Orhan; Baba, Alper; Cuevas, Raquel Marijuan; Gunduz, Orhan (Academic Press Ltd- Elsevier Science Ltd, 2025)
Nature-based Solutions (NbS) are increasingly recognized for their role in the sustainable management of water resources, especially in Mediterranean regions facing seasonal water scarcity. While their benefits for biodiversity and climate resilience are well documented, there is little research on their application in small island regions where ecological fragility and water scarcity intersect. This study fills this gap by investigating the potential of NbS, particularly rainwater harvesting systems, on the island of Bozcaada (T & uuml;rkiye). A high-resolution Digital Elevation Model (DEM) was developed to delineate the watersheds of the island and analyze the water flow patterns. These watersheds were analyzed for their water retention potential and suitability for rainwater storage. The geological structure, soil type and native biodiversity were included in the site selection process to ensure ecological compatibility. Based on this analysis, optimal locations for ponds were identified and designed to support groundwater recharge and preserve local ecosystems. The results show that strategically placed rainwater ponds can improve seasonal water availability, reduce dependence on external sources and support native species throughout the year. This NbS-based approach provides a replicable framework for sustainable water management on small Mediterranean islands, emphasizing ecological integration and long-term resilience.
Gunduz, Orhan/0000-0001-6302-0277
Keywords: Water Management; Rainwater Harvesting; Island Ecosystem; Mediterranean; Nbs